Assessment of the Frequency of Worst Case Flow Conditions During Downstream Migration of Salmon Smolts at Bellows Falls Dam - Saunders, W P (ScholarWorks@UMass Amherst, 1987)
None supplied. Executive summary: This study examined the frequency of occurrence of worst case conditions for downstream migration of Atlantic salmon smolts at Bellows Falls Station. Worst case conditions were defined as river flows of less than 11,000 cfs (when all river flow is diverted through the power canal) during the likely period of smolt migration. The analysis was based on historical daily water temperature and daily river discharge data for Bellows Falls Dam. Daily river discharge data for White River Junction, VT also were examined. The likely period of smolt migration was defined in relation to a lower temperature limit of 50ºF (10ºC) and an upper limit of 68ºF (20ºC). Based on the median dates on which temperatures reached or exceeded these limits during a 19-year period at Bellows Falls, the likely migration period was defined as April 27 through June 14 of each year. Peak smolt passage probably occurs during the early part of this period. Frequencies of river discharges associated with worst case conditions during the likely period of downstream smolt migration were determined for each of 73 years of actual or predicted discharge data. An analysis of the frequencies of worst case conditions across years was developed. In most years, worst case conditions are likely to occur at some time during the likely period of smolt migration. The probability of worst case conditions during the likely period of smolt migration is 41 percent.